The Effect of Grit on Subjective Well-being Among Working College Students - Tiara Tami Putri; Hanny Hanny Rufaidah Damra; Iftita Rahmi (Universitas Negeri Semarang, 2026)
The increasing number of students who are pursuing their studies while working indicates that students are not only faced with academic demands but also with responsibilities in the workplace. This situation has the potential to affect subjective well-being, especially when students must balance these various demands. One psychological resource believed to play a role in maintaining subjective well-being is grit—a trait characterized by consistent interest and perseverance in achieving long-term goals. This study aims to examine the effect of grit on subjective well-being among working students. The study employs a quantitative approach using simple linear regression, involving 388 active students in Indonesia who are pursuing their studies while working. Data were collected using the Short Grit Scale (Grit-S) to measure grit, the Satisfaction with Life Scale (SWLS) to measure the cognitive dimension of subjective well-being, and the Scale of Positive and Negative Experience (SPANE) to measure the affective dimension of subjective well-being. The results indicate that grit has a significant effect on both the cognitive and affective dimensions of subjective well-being (p < 0.05). These findings suggest that working students with higher levels of grit tend to have greater life satisfaction and more positive emotional experiences.